Associations of Probiotic Fermented Milk (PFM) and Yogurt Consumption with Bifidobacterium and Lactobacillus Components of the Gut Microbiota in Healthy Adults - Redondo-Useros, Noemí; Gheorghe, Alina; Díaz-Prieto, Ligia E.; Villavisencio, Brenda; Marcos, Ascensión; Nova, Esther (Nutrients, 2019)
The current study investigates whether probiotic fermented milk (PFM) and yogurt consumption (YC) are related to both the ingested bacteria taxa and the overall gut microbiota (GM) composition in healthy adults. PFM and YC habits were analyzed in 260 subjects (51% male) by specific questionnaires, and the following groups were considered: (1) PFM groups: nonconsumers (PFM-NC, n = 175) and consumers (PFM, n = 85), divided as follows: Bifidobacterium-containing PFM (Bif-PFM; n = 33), Lactobacillus-containing PFM (Lb-PFM; n = 14), and mixed Bifidobacterium and Lactobacillus-containing PFM (Mixed-PFM; n = 38); (2) PFM-NC were classified as: yogurt nonconsumers (Y-NC; n = 40) and yogurt consumers (n = 135). GM was analyzed through 16S rRNA sequencing. PFM consumers showed higher Bifidobacteria taxa levels compared to NC, from phylum through to species. Specifically, Bif-PFM consumption was related to higher B. animalis levels (p < 0.001), whereas Lb-PFM consumption was associated to higher levels of Bifidobacterium (p < 0.045) and B. longum (p = 0.011). YC was related to higher levels of the yogurt starter Streptococcus thermophilus (p < 0.001). Lactobacilli and the overall GM were not related either to YC or PFM consumption. According to these results, healthy adults might benefit from PFM intake by increasing Bifidobacterium levels.